Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top
up vote 6 down vote accepted

Multiply by three the second equation and add this to the first one, and you'll get (check this!)

$$(x+y)^3=152+360=512=2^9\implies x+y=2^3=8$$

Now take it from here.

share|cite|improve this answer
Your method is perfectly OK, thanks. I got, $(x,y)={(3,5),(5,3)}$. I just have to ask, how did you see that relationship ? – David Sebastian Feb 23 '14 at 11:37
Experience, @DavidSebastian (years don't pass by in vain...). The first equation is ugly: cubics aren't the nicest people out there, but the second one heavily reminds Newton's binomial theorem for $\;(x+y)^3\;$, and multiplying it by three does the trick. That we get $\;512=2^9=$ a perfect cube on the other side is nice, but irrelevant for the general outcome. – DonAntonio Feb 23 '14 at 11:40
That's very cool DonAntonio. Before asking this question I tried to solve the problem like this. $x$ can be isolated in the first equation. So I get $x=\sqrt[3]{152-y^3}$. Then I substituted that in the second equation. By doing that I got $(\sqrt[3]{152-y^3})^2y+(\sqrt[3]{152-y^3})y^2=120$. But I think this expression is not solvable, right ? – David Sebastian Feb 23 '14 at 11:49

Here is another way through, which simply depends on seeing the factor $x+y$ in both parts of what is given, reducing the cubic to a quadratic as follows (though the elimination of the constant term will always give a homogeneous cubic even without noticing this factor):

$x^3+y^3=(x^2-xy+y^2)(x+y)=152=8\times 19$

$x^2y+xy^2=(x+y)xy=120=8\times 15$

Multiply the first equation by $15$ and the second by $19$ to obtain:


Then we either have $x=-y$, which is easily eliminated, or divide through by $x+y\neq 0$ to give $$15x^2-34xy+15y^2=0$$ which factorises (quadratic formula) as $$(5x-3y)(3x-5y)=0$$

Either of these factors gives a linear relation which can be plugged into either of the original equations to give a solution.

share|cite|improve this answer
Just to note (might be useful), equations of the form $ax^2+bxy+cy^2=0$ can be solved by dividing both sides by $y^2$ (where $y\neq 0$) and then solving a quadratic equation in terms of $\frac{x}{y}$. – user26486 Feb 23 '14 at 19:23

Another method :

Suppose $x,y$ be the roots of $z^2+az+b=0$

$x+y=-a$ and $xy=b$




$a=-8$ and $b=120/8=15$

Solve of $z^2-8z+15=0$ for $x$ and $y$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.